Competitiveness, market and State - Vera Vasallo, Alejandro (2007)
Development planning must propose economic dynamism with institutional development, social equity with human capital formation, and international competitiveness based on technical progress. The principle that must be followed is "as much of the market as possible and as much of the State as necessary", so that sometimes State intervention is essential for competitive performance in the market.